Effects of Code Switching Among College Instructors and Students in a Philippine Classroom Setting - Louie B. Villanueva; Bert A. Gamiao (The English Teacher, 2022)
This study explored the effects of code-switching among Filipino college instructors and students and identified some implications of the effects of code-switching in Philippine college classrooms. Using descriptive-qualitative analysis and in-depth interview (IDI), the researchers examined the effects of code-switching among Filipino college instructors and students. This approach seeks to describe, decode, translate, and otherwise come to terms with the meaning of certain more or less naturally occurring phenomena in the social world. The following effects to teaching and learning were inferred: code switching helps students to better understand directions, eradicates language barrier for a clearer instruction, promotes better understanding by students, helps them in generating a better choice, ensures semantic understanding among students, and aids the students to investigate further, to clarify, to verify, or to confirm an earlier knowledge. All of these are directed towards achieving a better performance of the teachers and students. This study implicates that the use of code switching can facilitate teaching and learning in Philippine college classrooms.